2020
DOI: 10.1161/hypertensionaha.119.13197
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Renin-Angiotensin-Aldosterone System Inhibitors on Short-Term Mortality After Sepsis

Abstract: Antagonists of the renin-angiotensin-aldosterone system (RAAS), including ACEIs (angiotensin-converting enzyme inhibitors) and ARBs (angiotensin II receptor blockers), may prevent organ failure. We, therefore, investigated whether specific RAAS inhibitors are associated with reduced mortality in patients with sepsis.We conducted a population-based retrospective cohort study using multivariable propensity score–based regression to control for differences among patients using different RAAS inhibitors. A multiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 49 publications
2
59
0
1
Order By: Relevance
“…Because RAS blockade or beta blocker is recommended for the patient with cardiovascular complications, stopping these drugs may be harmful. In a recent retrospective population based cohort study, Hsu W, et al, reported that established RAS blockade therapy before sepsis will be protective for the sepsis related mortality [1]. These results seems to be in line with the recent study showing depressed sympathetic modulation can be a signal for sepsis in patient with infection [2].…”
Section: General Aspects Of Infection and Hypertension Managementsupporting
confidence: 61%
“…Because RAS blockade or beta blocker is recommended for the patient with cardiovascular complications, stopping these drugs may be harmful. In a recent retrospective population based cohort study, Hsu W, et al, reported that established RAS blockade therapy before sepsis will be protective for the sepsis related mortality [1]. These results seems to be in line with the recent study showing depressed sympathetic modulation can be a signal for sepsis in patient with infection [2].…”
Section: General Aspects Of Infection and Hypertension Managementsupporting
confidence: 61%
“…On the other hand, scientific societies recommend not to discontinue RAS inhibitors because of insufficient evidence of their potential harm and overwhelming evidence on their benefits 35‐39 and even some researchers advocate for the use of RAS inhibitors based on the fact that, through increasing the expression of ACE2, they counterbalance the reduction in pulmonary ACE2 provoked by the virus either through internalization with viral entry and/or downregulation of ACE2 enzyme during this process, which would lower the production of inflammatory cytokines, 40 thus exerting a protective role in lung injury 41 . Remarkably, RAS inhibitors have been shown to be associated with reduced mortality in patients with sepsis 42 . A study conducted by Henry C et al 43 have found a beneficial effect of ACEI/ARB in patients admitted with viral pneumonia, as they significantly reduced the pulmonary inflammatory response and cytokine release caused by virus infection.…”
Section: Resultsmentioning
confidence: 99%
“…The abnormal increase in Angiotensin II was related to hypertension and lung failure. In addition, RAS inhibitors have been shown to be associated with reduced mortality in patients with sepsis [9]. Angiotensin II positively regulates the expression of inflammatory cytokines through the activation of AT1R [10].…”
Section: Discussionmentioning
confidence: 99%